Socioeconomic Challenges of California Strawberry Production and Disease Resistant Cultivars - Guthman, Julie; Jiménez-Soto, Estelí (Frontiers in Sustainable Food Systems, 2021)
Strawberries are the 4th highest grossing crop in California and supply 90% of US strawberries. But the industry’s long reliance on the use of chemical fumigants to control soil disease, nematodes and weeds is being threatened by increased regulation of these fumigants, leading to urgent efforts to develop and test non-chemical alternatives to fumigation, such as disease resistant cultivars. Many of these technologies are promising ecologically, but making them economically viable for growers is more challenging, especially in light of the socioeconomic context of strawberry production in California that has created a state of lock-in for a sustainability transition. This paper discusses how the challenges of land prices, labor shortages, marketing standards, and low prices bear on cultivar selection. Based on qualitative interviews, we corroborate that strawberry growers operate under significant socioeconomic constraints in California, many of which are beyond their control. In addition, we find that most growers see high-yielding varieties as crucial to their economic viability with regard to land, labor, and marketing intermediaries and yet recognize that the focus on individual farm productivity works at cross purposes to the problem of poor prices. Disease resistant varieties do not at face value address the concerns voiced by most growers. Our findings suggest, however, that if some of the other pressures were exogenously mitigated, growers might be more inclined to experiment with and adopt disease resistant varieties, in combination with other approaches. The most promising policy avenues seem to therefore lie with support of grower revenues.